Ретроспективна оцінка орнітофауни Подільського Побужжя - Матвійчук, Олександр; Matviichuk, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті висвітлено результати вивчення сучасного видового складу авіфауни Подільського Побужжя. Упродовж 2000–2014 років у регіоні виявлено 243 види птахів. Під впливом антропогенного чинника з початку ХХ ст. 22 види зникли з меж досліджуваної території, 36 – змінили свій статус перебування на ній, а 21 вид зареєстровано тут уперше. The article highlights the structural changes in the species composition of the avifauna of individual territories Vinnytsia and Khmelnytsky regions belonging to the pool of Yuzhny Bug river. In the period from 2000 to 2014 found staying within the boundaries of the study area 243 species of birds belonging to 19 orders, 53 families and 132 genera. On the territory of the Podolsky Pobuzhzhia dominate breeding (110 species, 45,3 %) and sedentary (50 species, 20,6 %) birds that belong to the 8 species of fauna origin. The most numerous were the European species (81 species, 47,9 %) and transpalearktic species (44 species, 26 %). It was found that under the influence of anthropogenic transformation of natural ecosystems, direct and indirect effects of human activities on birds exerted during the twentieth century, the structure of the region’s avifauna has changed significantly. For example, 22 bird species have disappeared from the study area, and 36 have changed their residence status on it. At the same time, 21 species of birds were recorded here for the first time, including 7 species over the last century have expanded their range into the socket significant areas, including the territory of the Podolsky Pobuzhzhia. The article highlights the structural changes in the species composition of the avifauna of individual territories Vinnytsia and Khmelnytsky regions belonging to the pool of Yuzhny Bug river. In the period from 2000 to 2014 found staying within the boundaries of the study area 243 species of birds belonging to 19 orders, 53 families and 132 genera. On the territory of the Podolsky Pobuzhzhia dominate breeding (110 species, 45,3 %) and sedentary (50 species, 20,6 %) birds that belong to the 8 species of fauna origin. The most numerous were the European species (81 species, 47,9 %) and transpalearktic species (44 species, 26 %). It was found that under the influence of anthropogenic transformation of natural ecosystems, direct and indirect effects of human activities on birds exerted during the twentieth century, the structure of the region’s avifauna has changed significantly. For example, 22 bird species have disappeared from the study area, and 36 have changed their residence status on it. At the same time, 21 species of birds were recorded here for the first time, including 7 species over the last century have expanded their range into the socket significant areas, including the territory of the Podolsky Pobuzhzhia.
Retrospective Evaluation of the Avifauna of the Podolsky Pobuzhzhia
Keywords: орнітофауна; Подільське Побужжя; антропогенна трансформація; фауністичне походження; видовий склад; avifauna; Podolsky Pobuzhzhia; anthropogenic transformation; faunal origin; species composition